2015
DOI: 10.1007/s10616-015-9863-z
|View full text |Cite
|
Sign up to set email alerts
|

Direct and protective effects of single or combined addition of vincristine and ε-viniferin on human HepG2 cellular oxidative stress markers in vitro

Abstract: The objective of this study is to examine the direct effects of low doses and high doses of e-viniferin, a substance known to be an antioxidant, and vincristine sulphate, a chemotherapeutic agent, alone and in combination [e-viniferin ? vincristine] on HepG2 cell strain, as well as evaluate oxidative stress after incubation periods of 3, 6, and 24 h. Direct effect was determined right after the incubation period; however, for protective effect, antioxidant protection response was determined after the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…ε-viniferin is probably the most studied form of viniferin, due to its many biological activities [ 5 ], such as anti-inflammatory [ 6 ], antioxidant [ 7 ], antineoplasic [ 8 ], antiobesity [ 9 ], cardioprotective [ 10 ] and neuroprotective actions [ 11 ]. As occurred with resveratrol, it was first described in grapevine leaves by Langcake and Price in 1977, who observed that it is a resveratrol dehydrodimer synthesized via oxidative cyclization [ 12 ].…”
Section: Chemical Structure Of Viniferinmentioning
confidence: 99%
“…ε-viniferin is probably the most studied form of viniferin, due to its many biological activities [ 5 ], such as anti-inflammatory [ 6 ], antioxidant [ 7 ], antineoplasic [ 8 ], antiobesity [ 9 ], cardioprotective [ 10 ] and neuroprotective actions [ 11 ]. As occurred with resveratrol, it was first described in grapevine leaves by Langcake and Price in 1977, who observed that it is a resveratrol dehydrodimer synthesized via oxidative cyclization [ 12 ].…”
Section: Chemical Structure Of Viniferinmentioning
confidence: 99%